Intra-articular glucocorticoid injection site: best practice guidelines - N. V. Chichasova; A. M. Lila (Медицинский совет, 2021)
The article presents modern recommendations for the use of systemic administration of glucocorticoids. It is indicated that there is a clear tendency to minimize the doses and timing of the appointment of systemic glucocorticoids in rheumatoid arthritis, and in seronegative spondyloarthropathies (ankylosing spondylitis, psoriatic arthritis), in accordance with both foreign and domestic recommendations, systemic therapy with glucocorticoids is not carried out. It is emphasized that at the present stage, the role of local administration of glucocorticoids will increase as an effective way to reduce the activity of arthritis in any nosologically form. The mechanisms of action of locally administered glucocorticoids leading to anti-inflammatory and analgesic effects are described. The comparative characteristics of locally administered glucocorticoids with different duration of action according to their effectiveness and safety are presented. Predictors of the effectiveness of local therapy with glucocorticoids are described. The data on the evaluation of the duration of the anti-inflammatory and analgesic effects of various local glucocorticoids, including in comparison with the intra-articular administration of hyaluronic acid preparations, which showed the advantages of betamethasone over triamcinolone acetate, are presented. The differences in the crystal structure of betamethasone and triamcinolone acetate are described. It is indicated that the 2.5-fold smaller size of betamethasone crystals compared to triamcinolone acetate crystals and the absence of betamethasone crystals makes it possible to use betamethasone in the treatment of inflammatory processes in periarticular tissues, as well as in crystalline arthritis (gout, pseudogout). The data on the safety of the use of intra-articular injection of glucocorticoids are presented. It is indicated that the registration in the Russian Federation of a new form of betamethasone in pre-filled syringes makes it even more possible to avoid infectious complications of this type of therapy. Rare cases of complications of local therapy with glucocorticoids are described.